2017
DOI: 10.1182/blood-2017-02-766691
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET–driven consolidation strategy in diffuse large B-cell lymphoma: final results of a randomized phase 2 study

Abstract: Key Points• Superiority of R-ACVBP over R-CHOP14 was not established, as IHP criteria driving consolidation did not properly reflect disease control.• The 26% PET2 2 /PET4 2 patients using IHP criteria increased to 79% using DSUVmax, which may help better select those needing an alternative to SIC.Dose-dense induction and up-front consolidation with autologous stem cell transplantation (ASCT) remain controversial issues when treating patients with high-risk diffuse large B-cell lymphoma. GELA designed a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 23 publications
8
84
0
Order By: Relevance
“…Non-responders underwent salvage treatment according to local investigators. Based on the exploratory results of the LNH2007-3B study [51], PET positivity was defined as a decline of SUV max in an FDG-avid target lesion of at least 66% or 70% from baseline to PET after 2 and 4 cycles of chemotherapy, respectively. This trial aimed to validate the ∆SUV max -driven consolidation in young patients with high-risk disease.…”
Section: Dlbclmentioning
confidence: 99%
“…Non-responders underwent salvage treatment according to local investigators. Based on the exploratory results of the LNH2007-3B study [51], PET positivity was defined as a decline of SUV max in an FDG-avid target lesion of at least 66% or 70% from baseline to PET after 2 and 4 cycles of chemotherapy, respectively. This trial aimed to validate the ∆SUV max -driven consolidation in young patients with high-risk disease.…”
Section: Dlbclmentioning
confidence: 99%
“…Interim PET has been evaluated as a possible biomarker of early R‐CHOP success or failure in several retrospective and prospective studies. About 39–87% patients achieve a negative interim FDG‐PET/CT in prospective studies of advanced stage DLBCL initially receiving R‐CHOP, as shown in Table . The rate of interim FDG‐PET/CT negativity is very broad due to significant heterogeneity between studies, including variable timing of the interim PET (after 2, 3, or 4 cycles) as well as variable interpretation criteria with different definitions of FDG‐PET/CT positivity (internal visual point systems, International Harmonization Project criteria, Deauville criteria).…”
Section: Interim Fdg‐pet/ct Response Adapted Treatment Strategiesmentioning
confidence: 99%
“…Using an interim positron emission tomography (PET)-adapted approach to consolidation therapy, they show that quantitative rather than qualitative PET assessment may better select some patients needing alternative treatments, including autologous stem cell transplantation (ASCT). 1 …”
mentioning
confidence: 99%
“…1 In recent years, gene therapy for blood cell diseases in which autologous hematopoietic stem cells (HSCs) are corrected using a lentiviral vector has led to clinical benefits similar to those from allogeneic transplant. Much of the focus has been on severe diseases affecting infants and young children (severe combined immunodeficiency, X-linked adrenoleukodystrophy, metachromatic leukodystrophy) in which early intervention has the potential to prevent the…”
mentioning
confidence: 99%